PENDIDIKAN TAREKAT PERSPEKTIF KH. ACHMAD ASRORI AL-ISHAQY DAN RELEVANSINYA TERHADAP TUJUAN PENDIDIKAN NASIONAL - Nashiruddin, Nashiruddin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2018)
Life in modern times is often lulled by a lifestyleglamorous. As a result the heart is easily caught up in the mental illness and increasinglyempty of serenity. Therefore, a doctor is neededexperts in their fields to deal with these problems.Doctors in this case are Sufi scholars who have teacher titlestarekat. KH. Achmad Asrori al-Ishaqi is one of the teacherstarekat whose teachings are currently developing. However, stillthere are some people who think that lifestyleclosely inhibiting one's creativity, because in itteaches to keep away from worldly affairs, which it does notin accordance with the national education goals that sound"Develop Creativity". Based on the description,considered urgent for researching the education of the tarekatled by KH. Achmad Asrori, about the purpose of national education,and about the relevance of KH. Achmad Asroritowards national education goals. This research aims todescribe the perspective education of KH. Achmad Asrori,national education goals, and relevance of tarekat educationperspective of KH. Achmad Asrori towards national education goals.The approach or method used in this study isLibrary Research (library research). Because data will be extractedfrom library data, namely, books by KH. Achmad Asrori,books about educational goals, and other datasupport. The results of the study indicate that the essence of Educationperspective KH. Achmad Asrori al-Ishaqi is educationmorality or karkter through perfection of adab with a barometer of sufiyyah behavior that uses practical methods, namely,practice of dhikir or wirid in the guidance of the teacher of the murshidthere is a spiritual bond through mubaya'ah to cleanse the diseaseheart in order to be willing to Allah. The purpose of educationthe national goal that is to be achieved is to develop the potential of the citizensIndonesia as a whole to become a complete human being(al-Insan al-kamil) both in terms of material zahiriyyah and sidesbatiniyyah. While the relevance of the KH tarekat education. AchmadAsrori towards the aim of national education is that educationthe tarekat also formed an Indonesian citizencomplete through improvements in spiritual mental terms.